2017
DOI: 10.1002/lt.24770
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular vesicles from bone marrow–derived mesenchymal stem cells protect against murine hepatic ischemia/reperfusion injury

Abstract: Hepatic ischemia-reperfusion injury (IRI) and associated inflammation contributes to liver dysfunction and complications after liver surgery and transplantation. Mesenchymal stem cells (MSC) have been reported to reduce hepatic IRI because of their reparative immunomodulatory effects in injured tissues. Recent studies have highlighted beneficial effects of extracellular vesicles from MSCs (MSC-EV) on tissue injury. The effects of systemically administered mouse bone marrow derived MSC-EV were evaluated in an e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
79
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 106 publications
(85 citation statements)
references
References 46 publications
2
79
0
Order By: Relevance
“…Migratory responses and expression of activation markers in HSC are also stimulated by exosomes from, respectively, endothelial cells or other activated HSC [62,63]. In these prior studies, the observed responses were attributed to the uptake into the recipient cells and subsequent action of a variety of EV cargo molecules including CXCL10 [58] S1P [59,64], TRAIL [32], vanin-1 [60], CD40L [57], SK1/2[59,64], CCN2[25] or miRs [26]. An important feature of many of these findings is that the pathophysiology-related pathways were driven by EVs derived from cells that were injured (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Migratory responses and expression of activation markers in HSC are also stimulated by exosomes from, respectively, endothelial cells or other activated HSC [62,63]. In these prior studies, the observed responses were attributed to the uptake into the recipient cells and subsequent action of a variety of EV cargo molecules including CXCL10 [58] S1P [59,64], TRAIL [32], vanin-1 [60], CD40L [57], SK1/2[59,64], CCN2[25] or miRs [26]. An important feature of many of these findings is that the pathophysiology-related pathways were driven by EVs derived from cells that were injured (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…EVs derived from mesenchymal stem cells (MSCEVs) have been shown to improve the survival of mice with d‐galactosamine/TNF‐α‐induced lethal hepatic failure . MSCEVs have also been shown to be a protective treatment when administered before ischemic‐reperfusion liver injury in mice . Additionally, MSCEVs that contained the miRNA miR‐223 have been shown to have a protective effect in an experimental hepatitis mouse model as well .…”
Section: Discussionmentioning
confidence: 99%
“…Human MSCs can be obtained from bone marrow, umbilical cord, adipose tissues or other adult human tissues (5). Most studies to date have been based on the use of bone marrow derived MSC.…”
mentioning
confidence: 99%
“…In another study carried out by the same group, a protective effect of BM-MSC-EV was observed with experimental hepatic ischemia/ reperfusion injury in vivo . The administration of MSC-EV in mice after 6-hours of reperfusion, reduced serum markers of hepatic injury, blood urea nitrogen and creatinine, and decreased caspase 3—positive cells (5). Similarly, Tan et al .…”
mentioning
confidence: 99%
See 1 more Smart Citation